The complex interplay of local communities and global initiatives in Peatland management: An ethnography of frictional environmentality - Lubis, Zulkifli; Bahri, Saipul; Siregar, Muhammad Bangun; Rangkuti, Zoraya Alfathin (Research Journal in Advanced Humanities, 2026)
Peatland restoration has become a central strategy in global climate governance, yet its implementation often generates tension between universal environmental goals and local socio-cultural realities. This study examines the complex interplay between global initiatives and local communities in peatland management in Central Kalimantan, Indonesia, through an ethnographic lens. Drawing on the concept of frictional environmentality, it explores how competing rationalities, power relations, and knowledge systems shape the outcomes of the Kalimantan Forest and Climate Partnership (KFCP), a REDD+ pilot project. Using a multi-actor ethnographic approach that integrates environmental anthropology, political ecology, and Foucauldian governmentality, the research reveals that multiple forms of environmentality sovereign, disciplinary, neoliberal, and truth coexist and collide within the same governance arena. While KFCP embodies neoliberal and technocratic environmentalities emphasizing incentive-based conservation and carbon quantification, local Ngaju Dayak communities operate within truth environmentalities rooted in communal cosmologies and subsistence ethics. The resulting friction produces hybrid forms of environmental governance marked by pragmatic adaptation, selective participation, and the reappropriation of external rules to serve local interests. The study concludes that peatland restoration success depends not on imposing global models but on recognizing and negotiating these frictions as productive spaces for dialogue and hybrid governance. By advancing the concept of frictional environmentality, the paper contributes a nuanced understanding of how environmental subjects are formed, contested, and transformed within multi-scalar conservation regimes. This framework highlights the need for biocultural, participatory, and adaptive approaches that align global climate agendas with local ecological and cultural realities.